2020
DOI: 10.4103/apjon.apjon_46_19
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Screening and Prevention in Lesbian, Gay, Bisexual, and Transgendered Community and Asian Lesbian, Gay, Bisexual, and Transgendered Members

Abstract: Participation in cancer screening and prevention (cessation of or reduction in modifiable health risk behaviors) are the most effective methods of reducing cancer morbidity and mortality. Some members of the lesbian, gay, bisexual, and transgendered (LGBT) communities have not participated in screening for a variety of reasons which have been explored in the literature. Common and unique behavioral risks are also reviewed. Knowledge about Asian members of the LGBT community participation in cancer screening an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…This screening could be essential in the transgender community because people with HCV are asymptomatic and could pass on the disease to those around them and their sexual partners. By identifying these people, higher prevalence and transmission of this infection could be prevented with other transgender people or their other sexual partners, including lesbian, gay, bisexual, and other sexual minorities [ 20 , 40 42 ]. This study showed that the prevalence of HCV in Asian and American transgender people was higher than that of Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…This screening could be essential in the transgender community because people with HCV are asymptomatic and could pass on the disease to those around them and their sexual partners. By identifying these people, higher prevalence and transmission of this infection could be prevented with other transgender people or their other sexual partners, including lesbian, gay, bisexual, and other sexual minorities [ 20 , 40 42 ]. This study showed that the prevalence of HCV in Asian and American transgender people was higher than that of Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…This follows recognition of the vulnerability and unique concerns of this underserved patient population, who have a high rate of unmet needs ( 3 6 ). LGBTQI individuals are at higher risk of cancer compared with the general population ( 4 , 5 , 7 ), but are less likely to engage in cancer screening or have a regular healthcare provider ( 8 10 ). More specifically, LGBTQI patients report high levels of dissatisfaction with cancer healthcare ( 3 , 11 ), barriers to accessing cancer services ( 3 ), and difficulties in communication with HCPs ( 4 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…This screening could be essential in the transgender community because people with HCV are asymptomatic and could pass on the disease to those around them and their sexual partners. By identifying these people, higher prevalence and transmission of this infection could be prevented with other transgender people or their other sexual partners include lesbian, gay, bisexual, and other sexual minorities (18,(38)(39)(40). This study showed that the prevalence of HCV in Asian and American transgender people was higher than that of Europeans.…”
Section: Discussionmentioning
confidence: 67%